Family Integrated Care in Uganda: a feasibility study. Issue 3 (16th November 2022) - Duby, Jessica; Kabajaasi, Olive; Muteteri, Judith; Kisooka, Efulansi; Barth, Delaney; Feeley, Nancy; O'Brien, Karel; Nathan, Kenya-Mugisha; Tagoola, Abner; Wiens, Matthew O
Abstract : Objective: To determine the feasibility of adapting Family Integrated Care to a neonatal hospital unit in a low-income country. Design: Single-centre, pre/post-pilot study of an adapted Family Integrated Care programme in Uganda (UFICare). Setting: Special Care Nursery at a Ugandan hospital. Patients: Singleton, inborn neonates with birth weight ≥2 kg. Interventions: As part of UFICare, mothers weighed their infant daily, assessed for severe illness ('danger signs') twice daily and tracked feeds. Main outcome measures: Feasibility outcomes included maternal proficiency and completion of monitoring tasks. Secondary outcomes included maternal stress, discharge readiness and post-discharge healthcare seeking. Results: Fifty-three mother–infant dyads and 51 mother–infant dyads were included in the baseline and intervention groups, respectively. Most mothers were proficient in the tasks 2–4 days after training (weigh 43 of 51; assess danger signs 49 of 51; track feeds 49 of 51). Mothers documented their danger sign assessments 82% (IQR 71–100) of the expected times and documented feeds 83% (IQR 71–100) of hospital days. In the baseline group, nurses weighed babies 29% (IQR 18–50) of hospitalised days, while UFICare mothers weighed their babies 71% (IQR 57–80) of hospitalised days (p<0.001). UFICare mothers had higher Readiness for Discharge scores compared with the baseline group (baseline 6.8; UFICare 7.9; p<0.001). There was no difference in maternal stress scores or post-discharge healthcare seeking. Conclusions: Ugandan mothers can collaborate in the medical care of their hospitalised infant. By performing tasks identified as important for infant care, mothers felt more prepared to care for their infant at discharge.